The Political Economy of the Opioid Epidemic - Cuéllar, Mariano-Florentino (2020)
Public health problems have a political economy rooted largely in public and private laws that both reflect the distribution of power in society and shape its policy responses. In this Article, we apply this perspective to the U.S. opioid crisis, which was triggered by a quadrupling of opioid prescribing beginning in the mid-1990s. Such staggering increases in opioid use are impossible to understand without unpacking the incentives and institutional pressures associated with the distribution and use of addictive legal drugs, particularly how those pressures can dilute the substantive goals and efficacy of regulatory governance